A study of Growth of modern education during colonial period - Sharmila (Innovative Research Thoughts, 2018)
Educating a country's population is crucial to that country's progress. After the British occupied Manipur in the late 19th century, colonial education (especially western education) made its way there. Because to colonialism, the educational system underwent profound modifications. This dissertation aims to provide light on the evolution of educational institutions and the profound changes that occurred as a result of education throughout the colonial era The British, who first arrived as merchants but eventually assumed political power in India, had a profound impact on the country's history and culture. Despite India's status as one of the British Empire's most extensive possessions, the country ranked at the bottom in the world in terms of government initiatives and investments in human capital. Until the early nineteenth century, the East India Company showed a general lack of interest in the establishment of schools in India, despite the country's dire educational needs. They first prioritized funding for institutions of classical education and western scientific research. It was also considered important by the British administration that the corporation do its part in advancing the English language in India. This was done with the hope that a new generation of well-educated Indians would emerge to meet the needs of bureaucratic institutions. Macaulay's (1835) educational theory was used as a tool of colonization. Fundamentally, it destroyed Indians' confidence in their own heritage and altered their worldview to one that is at odds with their own culture and way of life.